Preliminary on-farm research - National Bean Programme (National Bean Programme, 1990)
The Malawi Bean Program distributed improved bean var. Sapelekedwa, Nasaka, 8-7, 5-2, and 25-2 x 8-7 among 5 farmers from the vicinity of Bunda College of Agriculture. Sapelekedwa (the only var. released by the program) gave the highest yields (900 kg/ha). Nyauzembe and White Type II (25-2 x 8-7) yielded half of Sapelekedwa. Problems associated with extension were observed and some recommendations are given to solve them. (CIAT)